2017
DOI: 10.1108/ics-03-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Organisational culture, procedural countermeasures, and employee security behaviour

Abstract: Purpose This paper provides new insights about security behaviour in selected US and Irish organisations by investigating how organisational culture and procedural security countermeasures tend to influence employee security actions. An increasing number of information security breaches in organisations presents a serious threat to the confidentiality of personal and commercially sensitive data. While recent research shows that humans are the weakest link in the security chain and the root cause of a great por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Moreover, this view lacks reliability due to the lack of consensus on the shared cultural values for the assessment of information security culture. This view has an added value of fruitfulness as it contributes to the development of research that is based on national cultures [24] such as crosscultural studies [52] and those based on organizational culture [10,47]. The action-based view.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this view lacks reliability due to the lack of consensus on the shared cultural values for the assessment of information security culture. This view has an added value of fruitfulness as it contributes to the development of research that is based on national cultures [24] such as crosscultural studies [52] and those based on organizational culture [10,47]. The action-based view.…”
Section: Discussionmentioning
confidence: 99%
“…This ISC is developed, learned and changes with time with the aim to protect information assets and preserve confidentiality, integrity, and availability of information and information systems resources so as meet to the core organization vision" [38] but they emphasized on a set of shared values in the organization. For instance, Connolly et al [10] investigated the impact of organizational values such as people-orientation, solidarity, sociability, task orientation and flat [31] on individual security behaviors. Tang, Li, & Zhan [47] defined information security culture by using values-based dimensions such as accountability, communication, compliance and governance.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…The articles listed in this subcategory focuses on the habitual practice of doing things by the organizations and its individuals. The way things are done around here is the common theme found in the articles about organizational culture [48,52]. The way things are done around here to protect organizational information assets is the common theme to describe information security culture [48,53,54].…”
Section: Classificationmentioning
confidence: 99%
“…Prior studies have found that security policies and security education can reduce the level of information systems misuse (Connolly, Lang, Gathegi, & Tygar, 2017;Hovav & D 'Arcy, 2012) but the mere existence alone of security policies without proper governance is ineffective (Da Veiga & Eloff, 2007;Shaaban & Conrad, 2013). In their proposed research agenda for information security, Crossler et al (2013) suggest that "it is likely those who are in high-power distance cultures are more readily willing to comply with detailed policy requirements, whereas those from low-power distance cultures are likely to pick-and-choose which policies they feel they should obey."…”
Section: Power Distancementioning
confidence: 99%